Highly Sensitive Label-Free Electrochemical Aptasensor Based on Screen-Printed Electrode for Detection of Cadmium (II) Ions. Issue 6 (1st January 2019) - Li, Yu; Ran, Guojing; Lu, Gen; Ni, Xinyu; Liu, Daling; Sun, Jianxia; Xie, Chunfang; Yao, Dongsheng; Bai, Weibin
Abstract : In this study, a simple but highly sensitive label-free aptasensor based on a screen-printed electrode (SPE) was developed for detection of Cd 2+ . As crucial biorecognizer, the Cd 2+ aptamer (issAP08-Cd 2+ ) was first screened out using the isothermal titration calorimetric method, which showed that the equilibrium dissociation constant (KD ) of Cd 2+ binding with issAP08-Cd 2+ was 2.9 μM. Then, the issAP08-Cd 2+, which is a single-stranded DNA with 25 nucleotides, was modified with thiol and assembled on gold screen-printed electrode. After that, the electrochemical aptasensor was used for Cd 2+ detection by dropping Cd 2+ solution on the SPE. The electrochemical properties were characterized by cyclic voltammetry (CV) and differential pulse voltammetry (DPV). Under the optimal conditions, the change of DPV peak currents density values (Δi) increased linearly with the logarithm of Cd 2+ concentrations from 0.1 ng/mL to 1000 ng/mL. The regression coefficient was 0.9914 and the limit of detection (LOD) was 0.05 ng/mL (S/N = 3). This outcome supported the conclusion that the electrochemical aptasensor not only showed good sensitivity and selectivity but also obtained satisfactory reproducibility and stability results and performance on applications in real samples. More importantly, the composition of this aptasensor is very simple, and it has promising potential for rapid field detection of Cd 2+ .